PENGARUH PENERAPAN PRUDENTIAL BANKING PRINCIPLE DALAM MEMINIMALISIR RISIKO KREDIT BERMASALAH PADA PD. BPR NTB SUMBAWA - Sapriadi, S; Usman, U (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to examine the effect of the implementation of the prudential banking principle in minimizing the risk of non-performing loans at PD. BPR NTB Sumbawa. The type of this study was causal associative research. The type of data used was quantitative data obtained directly from research respondents. The population in this study was all employees at PD. BPR NTB Sumbawa, totaling 98 people. This study used a census sampling or saturated sampling technique, so that the respondents in this study numbered 98 people. The data used in this study were collected using a questionnaire to be analyzed using techniques including simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of data analysis in this study, it is known that the t-value calculated of the hypothesis testing results was 8.151, which was greater than the t table value of 1.661 (8.151>1.661), while the significance value was 0.000, which was smaller than the real level value of 0.05 (0.000<0.05). Based on these results, it can be stated that the implementation of the prudential banking principle had a positive and significant effect on the risk of non-performing loans at PD. BPR NTB Sumbawa. The implementation of the prudential banking principle had a fairly large ability to minimize the risk of non-performing loans at PD. BPR NTB Sumbawa, which was 40.9%, while the remaining of 59.1% was effected by other variables outside this research model.